Renascent Entrepreneurship - Entrepreneurial Preferences Subsequent to Firm Exit - Erik Stam; David B. Audretsch; Joris Meijaard (Max Planck Institute of Economics, 2006)
Why should individuals that have exited their firm consider re-entering into entrepreneurship, i.e. become renascent entrepreneurs? According to the logic of economic models of firm dynamics there is no reason to re-enter into entrepreneurship following termination of a previous firm. In contrast, research on nascent entrepreneurship has shown the positive effect of entrepreneurial experience on planning a new firm start. Based on the empirical evidence from a database consisting of ex-entrepreneurs, this study shows that renascent entrepreneurship is a pervasive phenomenon in current society. Especially entrepreneurial human and social capital induce renascent entrepreneurship. In addition, the nature of the firm exit also affects the probability of renascent entrepreneurship.
Keywords: 330; entrepreneurial preferences; entrepreneurial skills; firm exit; renascent entrepreneurship; economics of entrepreneurship; Unternehmensgründung; Konkurs; Marktaustritt; Unternehmensentwicklung; Unternehmer; Welt